Historical Synthesis-Analysis of Changes in Grain Nitrogen Dynamics in Sorghum - Ciampitti, Ignacio A.; Prasad, P. V. Vara (Frontiers in Plant Science, 2016)
Unraveling the complexity underpinning nitrogen (N) use efficiency (NUE) can be physiologically approached via examining grain N sources and N internal efficiency (NIE) (yield to plant N content ratio). The main objective of this review paper is to document and understand sorghum NUE and physiological mechanisms related to grain N dynamics. The study of different grain N sources, herein defined as the reproductive-stage shoot N remobilization (Remobilized N), reproductive-stage whole-plant N content (Reproductive N), and vegetative-stage whole-plant N content (Vegetative N), was pursued with the goal of synthesizing scientific literature for sorghum [Sorghum bicolor (L.) Moench] crop. A detailed literature review was performed and summarized on sorghum NUE (13 studies; >250 means) with three Eras, defined by the year of the study, named as Old Era (1965-1980); Transient Era (1981-2000); and New Era (2001-2014). The most remarkable outcomes from this synthesis were: 1) overall historical (1965-2014) cumulative yield gain was > 0.5 Mg ha-1 (yields >7 Mg ha-1); 2) NIE did not change across the same time period; 3) grain N concentration (grain %N) accounted for a large proportion (63%) of the variation in NIE; 4) NIE increased as grain %N diminished, regardless of the Eras; 5) Remobilized N was strongly (>R2 0.6) and positively associated with Vegetative N, presenting a unique slope across Eras; and 6) a trade-off was documented for the Remobilized N and Reproductive N (with large variation, <R2) relationship, suggesting complex regulation processes governing N forces. Improvements in NUE are subjected to the interplay between N supply (N from non-reproductive organs) and grain N demand, sink- (driven by grain number) and source-modulated (via restriction of grain N demand).